2017
DOI: 10.1104/pp.17.00878
|View full text |Cite
|
Sign up to set email alerts
|

Type B Response Regulators Act As Central Integrators in Transcriptional Control of the Auxin Biosynthesis Enzyme TAA1

Abstract: During embryogenesis and organ formation, establishing proper gradient is critical for auxin function, which is achieved through coordinated regulation of both auxin metabolism and transport. Expression of auxin biosynthetic genes is often tissue specific and is regulated by environmental signals. However, the underlying regulatory mechanisms remain elusive. Here, we investigated the transcriptional regulation of a key auxin biosynthetic gene, l-Tryptophan aminotransferase of Arabidopsis1 (). A canonical and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 65 publications
0
44
0
Order By: Relevance
“…Cytokinin also modulates root growth (Kushwah et al ., ; Raines et al ., ). A recent report indicated that type‐B response regulators in cytokinin signaling functions in root growth by binding to the TAA1 promoter to regulate its transcription (Yan et al ., ). Also, this phytohormone can promote NO accumulation to inhibit root growth (Shen et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Cytokinin also modulates root growth (Kushwah et al ., ; Raines et al ., ). A recent report indicated that type‐B response regulators in cytokinin signaling functions in root growth by binding to the TAA1 promoter to regulate its transcription (Yan et al ., ). Also, this phytohormone can promote NO accumulation to inhibit root growth (Shen et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…B response regulators in cytokinin signaling functions in root growth by binding to the TAA1 promoter to regulate its transcription (Yan et al, 2017). Also, this phytohormone can promote NO accumulation to inhibit root growth (Shen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…An interaction of ARR2 and ARR14 has been described using a two-hybrid system in yeast (Dortay, Mehnert, Bürkle, Schmülling, & Heyl, 2006). Recently, it was found that the C-termini of ARR1 and ARR12 interact to regulate auxin synthesis (Yan et al, 2017). It could also be that interactions between type-B ARRs are context-dependent as it is known for the phosphorylation-dependent homodimerization of bacterial RRs (Mack, Gao, & Stock, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Beside the interaction amongst ARRs, interactions between several type-B ARRs and other proteins exist. For example, ARR1, ARR2 and ARR14 interact with the DELLA proteins RGA1 and GAI to regulate root development and photomorphogenesis (Marín-de la Rosa et al, 2015; Yan et al, 2017). During the regulation of auxin synthesis, EIN3 interacts with the C-terminus of ARR1 and thereby increases ARR1 activity (Yan et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation